2022
DOI: 10.1080/14789949.2022.2070523
|View full text |Cite
|
Sign up to set email alerts
|

Can measures of cognitive flexibility and inhibition distinguish forensic psychiatric inpatients from prisoners?

Abstract: We investigated whether forensic psychiatric inpatients can be distinguished from prisoners and healthy controls on the basis of their performance on cognitive tasks measuring cognitive flexibility (with a reversal learning task) and inhibition (with a stop signal task). Forensic psychiatric inpatients were expected to perform worse compared to prisoners. This study was based on pre-existing data from N = 241 males (119 forensic psychiatric inpatients, 57 prisoners and 65 healthy controls). We fitted logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Weaknesses in these cognitive domains have robust positive associations with aggressive and criminal behavior (Morgan & Lilienfeld, 2000; Ogilvie et al, 2011; Portnoy et al, 2013; Janes et al, 2024; Jansen & Franse, 2024). Similar results have been obtained in forensic (psychiatric) inpatient populations as well (Molleman, Driessen, et al, 2022; Molleman, Molleman, et al, 2022; Shumlich et al, 2019). However, recent research did not demonstrate any decrements in memory, orientation, language, and visuospatial skills within the prison and outpatient forensic (psychiatric) population (Fassaert et al, 2022).…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Weaknesses in these cognitive domains have robust positive associations with aggressive and criminal behavior (Morgan & Lilienfeld, 2000; Ogilvie et al, 2011; Portnoy et al, 2013; Janes et al, 2024; Jansen & Franse, 2024). Similar results have been obtained in forensic (psychiatric) inpatient populations as well (Molleman, Driessen, et al, 2022; Molleman, Molleman, et al, 2022; Shumlich et al, 2019). However, recent research did not demonstrate any decrements in memory, orientation, language, and visuospatial skills within the prison and outpatient forensic (psychiatric) population (Fassaert et al, 2022).…”
supporting
confidence: 86%
“…Even though several studies showed that forensic patients may have difficulties with abstract reasoning (Morgan & Lilienfeld, 2000; Ogilvie et al, 2011; Portnoy et al, 2013; Shumlich et al, 2019), we did not find any differences between the ForFACT group and the control group on the abstract reasoning item. Recent studies that examined similar forensic psychiatric populations compared to healthy controls (Molleman, Driessen, et al, 2022; Molleman, Molleman, et al, 2022; Shumlich et al, 2019), also found no differences in performance between the groups on items of abstract reasoning. Even though abstract reasoning is believed to be strongly associated with EF (e.g., Wachholz & Yassuda, 2011), there is no consensus in the literature.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Improvements in cognitive flexibility, working memory, and planning may have a significant impact on reducing violent behavior among inmates (Vadini et al, 2018 ; Molleman et al, 2022 ; Romero-Martínez et al, 2022 ). Specifically, enhancing these executive functions could help prisoners regulate their emotions, inhibit impulsive behavior, and plan and execute non-violent problem-solving strategies (Seruca and Silva, 2016 ; Valizadeh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, enhancing these executive functions could help prisoners regulate their emotions, inhibit impulsive behavior, and plan and execute non-violent problem-solving strategies (Seruca and Silva, 2016 ; Valizadeh et al, 2020 ). As a result, prisoners may be less likely to engage in violent behavior, both within prison and after their release (Meijers et al, 2018 ; Molleman et al, 2022 ). Moreover, improved cognitive functioning can lead to better decision-making skills and increased self-control, which are crucial for successful reintegration into society.…”
Section: Discussionmentioning
confidence: 99%